2010
DOI: 10.1071/dn10018
|View full text |Cite
|
Sign up to set email alerts
|

First record ofNeoscytalidium dimidiatumandN. novaehollandiaeonMangifera indicaandN. dimidiatumonFicus caricain Australia

Abstract: Neoscytalidium dimidiatum is reported for the first time in Australia associated with dieback of mango and common fig. Neoscytalidium novaehollandiae is reported for the first time associated with dieback of mango. Neoscytalidium dimidiatum has a wide geographical and host range. For example, it has been reported on Albizia lebbeck,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 5 publications
0
43
0
Order By: Relevance
“…The disease, however, was widespread in the region. Leavitt, 1990;Leavitt & Munnecke, 1987;Martin, Martin, de Francisco, & Cobos, 2009;Niekerk, Crous, Groenewald, Fourie, & Halleen, 2004;Phillips, 1998Phillips, , 2002Ray, Burgess, & Lanoiselet, 2010;Taylor, Hardy, Wood, & Burgess, 2005;Úrbez-Torres et al, 2006). Leavitt, 1990;Leavitt & Munnecke, 1987;Martin, Martin, de Francisco, & Cobos, 2009;Niekerk, Crous, Groenewald, Fourie, & Halleen, 2004;Phillips, 1998Phillips, , 2002Ray, Burgess, & Lanoiselet, 2010;Taylor, Hardy, Wood, & Burgess, 2005;Úrbez-Torres et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The disease, however, was widespread in the region. Leavitt, 1990;Leavitt & Munnecke, 1987;Martin, Martin, de Francisco, & Cobos, 2009;Niekerk, Crous, Groenewald, Fourie, & Halleen, 2004;Phillips, 1998Phillips, , 2002Ray, Burgess, & Lanoiselet, 2010;Taylor, Hardy, Wood, & Burgess, 2005;Úrbez-Torres et al, 2006). Leavitt, 1990;Leavitt & Munnecke, 1987;Martin, Martin, de Francisco, & Cobos, 2009;Niekerk, Crous, Groenewald, Fourie, & Halleen, 2004;Phillips, 1998Phillips, , 2002Ray, Burgess, & Lanoiselet, 2010;Taylor, Hardy, Wood, & Burgess, 2005;Úrbez-Torres et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Mango dieback in the north (N) and NW of Australia has been associated with N. dimidiatum and N. novaehollandiae (Ray et al 2010). Tip dieback has been reported in mango trees situated in Florida, associated with infection by B. dothidea (Ploetz et al 1996) and N. ribis (Ramos et al 1991;Ramos et al 1997;Prakash and Eckert 2001).…”
Section: Au)mentioning
confidence: 99%
“…All pathogens that were isolated from cankered mango stems produced lesions. On the mango fruit, (Ray et al 2010). Lasiodiplodia hormozganensis was recently described from M. indica and Olea sp in Iran (Abdollahzadeh et al 2010) and from non-native environments in Australia (originally identified as L. parva).…”
Section: Pathogenicity Trial On Fruitmentioning
confidence: 99%
“…It is only in recent times (late 1980's) that their endophytic nature has been established and studied . Neoscytalidium novaehollandiae has only been recently identified and has previously only been recorded causing disease in Mangifera indica L. (Ray et al 2010) and from asymptomatic branches (sapwood) of Acacia synchronica Maslin, Adansonia gibbosa F.Muell., Crotalaria medicaginea L. and Grevillia agrifolia A.Cunn. ex R.Br.…”
Section: Lasiodiplodia Parva L Pseudotheobromae Barriopsis Iranianmentioning
confidence: 99%
“…ex R.Br. in Western Australia (Pavlic et al 2008) whereas N. dimidiatum is a worldwide cosmopolitan pathogen with a large host range (Ray et al 2010;Al-Saadoon et al 2012;Chuang et al 2012;Lan et al 2012;Liu et al 2012;Machado et al 2012). …”
Section: Lasiodiplodia Parva L Pseudotheobromae Barriopsis Iranianmentioning
confidence: 99%